Targeted Incentives, Broad Impacts: Evidence from an E-commerce Platform - Xiang Hui; Meng Liu; Tat Chan (Center for Economic Studies and ifo Institute (CESifo), 2022)
Digital platforms sometimes offer incentives to a subset of sellers to nudge behavior, possibly affecting the behavior of all sellers in the equilibrium. In this paper, we study a policy change on a large e-commerce platform that offers financial incentives only to platform-certified sellers when they provide fast handling and generous return policies on their listings. We find that both targeted and non-targeted sellers become more likely to adopt the promoted behavior after the policy change. Exploiting a large number of markets on the platform, we find that in markets with a larger proportion of the targeted population—hence more affected by the policy change—non-targeted sellers are more likely to adopt the promoted behavior and experience a larger increase in sales and equilibrium prices. This finding is consistent with our key insight that a targeted incentive may increase demand for non-targeted sellers when both platform certificates and the promoted behaviors are quality signals. Our results have managerial implications for digital platforms that use targeted incentives.
Keywords: 330; targeted incentives; quality provision; signalling; demand expansion